A one-year survey on aflatoxin M1 in raw milk - P. Visciano; M. Schirone; A.M.A. Olivastri; R. Tofalo; G. Perpetuini; G. Suzzi (Chiriotti Editori, 2015)
In the year 2012, 288 raw milk samples were collected from six different dairy cow farms and analyzed for the presence of aflatoxin M1 (AFM1) using the ELISA technique. The AFM1 levels ranged from 5 to 25 ng/kg and the highest concentrations were found in autumn, with a significant difference (p<0.05) between February and November. The EU legal limit of 50 ng/kg has never been exceeded. Even if the results of the present study show a low risk for AFM1, its occurrence in dairy products has to be regularly monitored due to their importance as foodstuffs for people and children above all.